Triple 9 [videorecording (DVD)] - Affleck, Casey, 1975-; Ejiofor, Chiwetel, 1977-; Mackie, Anthony, 1978- (Universal Pictures Home Entertainment, 2016)
A bank robbery is just the tip of the iceberg when two cops in Atlanta start suspecting members of their own team are involved. Not knowing who to trust and how deep the corruption goes, time is ticking for them to uncover the truth, before they become the target for the next deadly job.